Nomination practice in Malaysia: a review on the requirements and conditions from Islamic perspective - Mohd Khairy Kamarudin; Azwan Abdullah; Siti Fariha Muhamad (Intercontinental Management Research Review, 2015)
Nomination is an important instrument in the estate planning. There are a few institutions offering this instrument to assist the heirs accelerating the process of claiming deceased’s estate such as Employee Provident Fund (EPF), Pilgrimage Fund and Takaful contribution. The nominee has the responsibility to claim the fund and distribute it to the legal heirs in line with Islamic law of inheritance (faraid). However, most of the nominees fail to fulfill their responsibility appropriately. Thus, the purpose of this study is to review the conditions and requirement of nominee The finding shows few issues have to be taken into consideration in the process of nomination and several circumstances due to irresponsible nominees. This study suggests the respective authorities to undertake additional effort in increasing the public awareness on these matters and the laws and regulations must be enacted.